Spatio-temporal variations in water quality of urban landscape waters in the plain city. Issue 1 (31st December 2022) - Li, Na; Li, Ming; Zhou, Feng; Ma, Xiaoxue; Lyu, Huihua
ABSTRACT: Urban landscape waters (ULWs) are important components of ecological city; however, eutrophication has become increasingly serious. In Yancheng city, an eco-civilized city, the spatiotemporal characteristics of water quality indexes and the eutrophication degree were evaluated in Julong lake (JL) artificial ecological restoration and campus natural landscape (YCIT) waters. Since ecological restoration in 2016, the seasonal average concentrations of N, P in JL waters have been significantly decreased by more than 70%, satisfying the standards for water quality with light eutrophication. Conversely, the European Flower Street (EFS) and YCIT waters were hyper eutrophic, severely exceeding the Grade V water quality standard. The spatial distribution of ULWs quality deterioration in the plain area indicated that the human activities and endogenous pollutions contributed to ULWs eutrophication because of sluices controlling and low flow rate. This study provided a scientific basis for controlling the ULWs eutrophication via integrated eco-remediation technology in plain cities.